The listening space: conception, perception and temporality in the music of Salvatore Sciarrino - Monducci, G (2021)
My research focuses on the music of the Italian composer Salvatore Sciarrino (Palermo, 1947), with regard to how the concept of space relates to matters of sound and temporality. My thesis looks at theories of auditory perception and conceptual metaphor theory in order to provide a framework in which to analyze Sciarrino's music.